Evaluation of the units that conform the wastewater treatment plant south Maracaibo - Cannen Cárdenas; Cristina Jaeger; Héctor Villasmil; Tomás Perruolo; Suher Yabroudi; Franklin López; Lenin Herrera; Olga Castejón (Revista Técnica de la Facultad de Ingeniería, 2010)
The objetive of this study was to evaluate a waste water treatment plat, in stationary state, located in a region with tropical climate. This plant in based on stabilization ponds distributed as follows: two anaerobic units in parallel, a facultative pond, two maduration ponds in series and a pound used as the effluent storage. To do this, a series of30 sampling were made during 9 weeks of influent and effluent of the plant in order to evaluate the treatment efficiency ofthe system. Values of pH, DO, and temperature were measured in situ, and BOD, COD, P-total, NTK. Arnmonia-N, TSS, VSS, Nitrites and Nitrates, TC and FC were measured in the laboratory. These analysis were made following standardized methods. The removal values were found: BOD (77%), COD (37%). P-total (29%), NTK (56%), N-amoniacal (86%), TSS (87%). VSS (84%). TC (six logarithmic units) y FC (five logarithmic units). The generation of nitrates and nitIites was not relevant. According to effective venezuelan environmental regulations, the plant effluent can be used with agricultural purposes and/or to be discharged into a water body, such as in this case, Maracaibo's Lake.